Co-solvation effect on the binding mode of the α-mangostin/β-cyclodextrin inclusion complex - Rungnim, Chompoonut; Phunpee, Sarunya; Kunaseth, Manaschai; Namuangruk, Supawadee; Rungsardthong, Kanin; Rungrotmongkol, Thanyada; Ruktanonchai, Uracha (Beilstein Journal of Organic Chemistry, 2015)
Cyclodextrins (CDs) have been extensively utilized as host molecules to enhance the solubility, stability and bioavailability of hydrophobic drug molecules through the formation of inclusion complexes. It was previously reported that the use of co-solvents in such studies may result in ternary (host:guest:co-solvent) complex formation. The objective of this work was to investigate the effect of ethanol as a co-solvent on the inclusion complex formation between α-mangostin (α-MGS) and β-CD, using both experimental and theoretical studies. Experimental phase-solubility studies were carried out in order to assess complex formation, with the mechanism of association being probed using a mathematical model. It was found that α-MGS was poorly soluble at low ethanol concentrations (0–10% v/v), but higher concentrations (10–40% v/v) resulted in better α-MGS solubility at all β-CD concentrations studied (0–10 mM). From the equilibrium constant calculation, the inclusion complex is still a binary complex (1:1), even in the presence of ethanol. The results from our theoretical study confirm that the binding mode is binary complex and the presence of ethanol as co-solvent enhances the solubility of α-MGS with some effects on the binding affinity with β-CD, depending on the concentration employed.
Keywords: α-mangostin; β-cyclodextrin; binary complex; inclusion complex